2017
DOI: 10.1210/jc.2016-3547
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting C-Terminal Peptide–Modified hGH (MOD-4023): Results of a Safety and Dose-Finding Study in GHD Children

Abstract: This study confirms the long-acting properties of MOD-4023 and shows a promising safety and tolerability profile. This provides support for initiation of a phase 3 study in GHD children using a single weekly injection of MOD-4023.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 22 publications
6
46
0
Order By: Relevance
“…Our PEG-rhGH’s molecular weight is 58–66 kDa (14). The treatment dosage of the long-acting weekly PEG-rhGH is not equivalent to a simple accumulation of daily dosage of the daily rhGH, and it has been suggested that for a long-acting rhGH formula, comparing its biological/physiological effects with those of daily rhGH would be more appropriate than a simple molar comparison (19). The long-term efficacy of PEG-rhGH in children with GHD needs to be explored further to assess its potential superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Our PEG-rhGH’s molecular weight is 58–66 kDa (14). The treatment dosage of the long-acting weekly PEG-rhGH is not equivalent to a simple accumulation of daily dosage of the daily rhGH, and it has been suggested that for a long-acting rhGH formula, comparing its biological/physiological effects with those of daily rhGH would be more appropriate than a simple molar comparison (19). The long-term efficacy of PEG-rhGH in children with GHD needs to be explored further to assess its potential superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Other inclusion and exclusion criteria are reported by Zelinska et al [5]. Children (Tables 1, 2) were randomized to 1 of 3 weekly doses of MOD-4023 (0.25, 0.48, or 0.66 mg/kg weekly; n = 41; 27 boys, 14 girls) or daily r-hGH (Genotropin, 0.034 mg/kg/day; n = 11; 8 boys, 3 girls).…”
Section: Methodsmentioning
confidence: 99%
“…The dose selection for this study was based on previous nonclinical and clinical studies . The data obtained from a phase 1 study in healthy adult men, a phase 2 study in adults with GHD, and a phase 2 study in GHD children provided a favorable safety profile and confirmed the adequacy of a weekly regimen of MOD‐4023, as reflected by normalizing IGF‐1 standard deviation score (SDS) values. The average effective dose that was shown to maintain adult men with GHD within the IGF‐1 SDS normal range was 2.5 mg. On the basis of these results and assuming a similar response in the Japanese population, the lowest dose in the present study (2.5 mg) was also used as the initial dose in an ongoing phase 3 study in GHD adults, whereas the middle and high doses potentially provided 3‐ and 6‐fold exposure margins, respectively, over the initial clinical dose.…”
Section: Methodsmentioning
confidence: 99%